Multiple Bone Metastases from Glioblastoma Multiforme without Local Brain Relapse: A Case Report and Review of the Literature. Issue 5 (September 2013) - Takanen, Silvia; Bangrazi, Caterina; Caiazzo, Rossella; Raffetto, Nicola; Tombolini, Vincenzo
Extracranial metastases from glioblastoma multiforme (GBM) are a very rare event, even if an increasing incidence has been documented. We report the case of a young woman with primary GBM who developed bone metastases without local brain relapse. Because of persistent headache and visual disturbances, in March 2011 the patient underwent magnetic resonance imaging (MRI) evidencing a temporoparietal mass, which was surgically resected. Histology revealed GBM. She was given concomitant chemoradiotherapy according to the Stupp regimen. After a 4-week break, the patient received 6 cycles of adjuvant temozolomide according to the standard 5-day schedule every 28 days. In December 2011 she complained of progressive low back pain, and MRI showed multiple bone metastases from primary GBM, confirmed by histology. Cases of metastatic GBM in concurrence with a primary brain tumor or local relapse are more common in the literature; only a few cases have been reported where extracranial metastases from GBM occurred without any relapse in the brain. Here we report our experience.